Airborne microplastic/nanoplastic research: a comprehensive Web of Science (WoS) data-driven bibliometric analysis - Tan, Huiyi; Mong, Guo Ren; Wong, Syie Luing; Wong, Keng Yinn; Sheng, Desmond Daniel Chin Vui; Nyakuma, Bemgba Bevan; Othman, Mohd Hafiz Dzarfan; Kek, Hong Yee; Abdull Razis, Ahmad Faizal; Abdul Wahab, Nur Haliza; Abdul Wahab, Roswanira; Lee, Kee Quen; et al. (2023)
This paper presents the landscape of research on airborne microplastics and nanoplastics (MPs/NPs) according to the bibliometric analysis of 147 documents issued between 2015 and 2021, extracted from the Web of Science database. The publications on airborne MPs/NPs have increased rapidly from 2015 onwards, which is largely due to the existence of funding support. Science of the Total Environment is one of the prominent journals in publishing related papers. China, England, the USA, and European Countries have produced a significant output of airborne MP/NP research works, which is associated with the availability of funding agencies regionally or nationally. The research hotspot on the topic ranges from the transport of airborne MPs/NPs to their deposition in the terrestrial or aquatic environments, along with the contamination of samples by indoor MPs/NPs. Most of the publications are either research or review papers related to MPs/NPs. It is crucial to share the understanding of global plastic pollution and its unfavorable effects on humankind by promoting awareness of the existence and impact of MPs/NPs. Funding agencies are vital in boosting the research development of airborne MPs/NPs. Some countries that are lacking funding support were able to publish research findings related to the field of interest, however, with lesser research output. Without sufficient fundings, some impactful publications may not be able to carry a substantial impact in sharing the findings and discoveries with the mass public.